Pengaruh Etos Kerja, Disiplin Kerja Terhadap Kinerja Karyawan UD. Madyo Lancar Kabupaten Kediri - Aries Saputra; Sonny Subroto; Nuril Aulia Munawaroh (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The progress of a company cannot be separated from the role of human resources which makes people superior and hopefully able to achieve what they want. When employees in a company do not perform well and competently, it results in the company's operations not being as effective or efficient as possible. One of them is related to Work Ethics, Work Discipline and Employee Performance. The aim of this research is to determine the influence of work ethic, work discipline and employee performance at Ud. Madyo Lancar. The sample for this research consisted of 35 employees, with a sampling technique using saturated samples. This research uses a quantitative approach method, then the data obtained is processed using SPSS 25. The research results show that work ethic does not have a significant effect on employee performance variables, with a t test value of 0.543 and a significance value of 0.951 > 0.05. Work discipline has a significant effect on employee performance variables as shown by the t test value of 30.327 with a significance of 0.000 <0.05.